THE OBLIGATIONS AND LIABILITIES OF NOTARIES IN PROVIDING SOCIAL SERVICES IN ACCORDANCE WITH THE IMPLEMENTATION OF THEIR POSITIONS - Ellyca; Winanto Wiryomartani (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Notary as a public official authorized to make authentic deeds is one of the practitioners in the field of law who is obliged to provide social services for the community, especially for the poor. The notary's obligation to provide social services can help provide legal certainty as a form of a rule of law because it can prevent disputes, especially in terms of land ownership, land control. In this research to ensure the implementation of an objective research and in accordance with applicable legal principles, this research uses normative juridical research methods with an approach through applicable laws and regulations or through a statute approach and general legal concepts or conceptual approach. This prevention can be done if people who are unable as legal subjects know clearly their rights and obligations and have access to legal services. However, in general, social services in the field of law are currently only in the form of free legal assistance for parties in litigation, while it is still rare to find social services in the form of consulting assistance or notary services which are still little known to the less fortunate. Result of this research is writing intended to examine the obligations and responsibilities of a notary in providing social services to the community, especially for people who can't afford it.